Effect of wear on the burst strength of l-80 steel casing - Irawan, S. (Institute of Physics Publishing, 2015)
Casing wear has recently become one of the areas of research interest in the oil and gas industry especially in extended reach well drilling. The burst strength of a worn out casing is one of the significantly affected mechanical properties and is yet an area where less research is done The most commonly used equations to calculate the resulting burst strength after wear are Barlow, the initial yield burst, the full yield burst and the rupture burst equations. The objective of this study was to estimate casing burst strength after wear through Finite Element Analysis (FEA). It included calculation and comparison of the different theoretical bursts pressures with the simulation results along with effect of different wear shapes on L-80 casing material. The von Misses stress was used in the estimation of the burst pressure. The result obtained shows that the casing burst strength decreases as the wear percentage increases. Moreover, the burst strength value of the casing obtained from the FEA has a higher value compared to the theoretical burst strength values. Casing with crescent shaped wear give the highest burst strength value when simulated under nonlinear analysis.